Effects of exercise based on ACSM recommendations on anxiety in children and adolescents: a meta-analysis of randomized controlled trials - Xian, Jinhua; Hu, Qing; Jiang, Bo (Frontiers in Physiology, 2026)
PurposeTo investigate the effects of different dosages of exercise on anxiety symptoms in children and adolescents.MethodsThe present study screened randomized controlled trials (RCTs) from PubMed, Embase, Web of Science and Cochrane Library databases. According to the suggestions of American College of Sports Medicine (ACSM), all included studies were categorised into a high and a low/uncertain adherence group. The random-effects model was adopted in the meta-analysis. Subgroup analyses were also conducted to explore the differences in outcomes.ResultsA total of 27 RCTs including 2022 participants were extracted and included for analysis. The results indicated that exercise interventions may have an anxiolytic effect in youth (SMD = −0.36, 95% CI: −0.58 to −0.15, p = 0.0009). According to the ACSM, 13 studies were classified into high adherence group, and 14 studies were classified into low/uncertain adherence group. Subgroup analysis showed that the anxiety reduction was significantly larger in high ACSM adherence group (SMD = −0.67, 95% CI: −1.10 to −0.23, p = 0.002) than in low/uncertain ACSM adherence group (SMD = −0.13, 95% CI: −0.33 to 0.07, p = 0.21). Furthermore, exercise interventions longer than 11 weeks showed significantly greater effects than those shorter than 11 weeks. Only interventions delivered at least three times per week and incorporating combined exercise modalities exerted anxiolytic effects. Moreover, exercise interventions significantly reduced anxiety symptoms in populations with physical illnesses.ConclusionThe meta-analysis demonstrated that exercise interventions showed significant anxiolytic effects in children and adolescents. Moreover, the anxiety reduction in the high ACSM adherence group was significantly larger than that in the low/uncertain ACSM adherence group.